2014
DOI: 10.1111/jora.12169
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Domain Content in Understanding Identity Development Processes

Abstract: The current studies examined the importance of domain content in the processes of identity development using two approaches—narrative and status. We examined personal narratives for identity domain content, the co‐occurrence of different contents, and the relations between content and processes, using two approaches to identity—status and narrative. Across two studies, 762 participants (average age = 19 years) and 2214 narratives, traditional ideological and interpersonal status domains were present, but so wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
84
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 73 publications
1
84
0
1
Order By: Relevance
“…In contrast, if the unit is the specific memory and each individual provide three memories, then the coding process will yield three sets of final codes per participant. This type of data structure requires analytic decisions, which include aggregating the codes across memories to create singular individual scores (e.g., McAdams et al, 2004;Waters & Fivish, 2014) or using multi-level modeling, nesting memories within individuals (e.g., McLean & Fournier, 2008;McLean, Syed, Yoder & Greenhoot, 2014). A major advantage of the latter approach is that it allows for analyses both within and between individuals, and therefore can address a wider variety of research questions.…”
Section: The Coding Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, if the unit is the specific memory and each individual provide three memories, then the coding process will yield three sets of final codes per participant. This type of data structure requires analytic decisions, which include aggregating the codes across memories to create singular individual scores (e.g., McAdams et al, 2004;Waters & Fivish, 2014) or using multi-level modeling, nesting memories within individuals (e.g., McLean & Fournier, 2008;McLean, Syed, Yoder & Greenhoot, 2014). A major advantage of the latter approach is that it allows for analyses both within and between individuals, and therefore can address a wider variety of research questions.…”
Section: The Coding Processmentioning
confidence: 99%
“…The theory-driven approach involves deconstructing an existing psychological theory into codes that can be applied to the data whereas the data-driven approach involves the construction of a coding scheme based on the data collected. For example, the theory-driven approach was used by McLean et al (2014) to develop narrative coding for domain-specific identity development originally specified by Marcia (1966Marcia ( , 1993 and other identity status theorists. In contrast, Syed and Azmita (2008) used the inductive or data-driven approach to find common themes in narratives about ethnicity related experiences using a diverse group of readers.…”
Section: The Coding Processmentioning
confidence: 99%
“…Thus, as adolescents or adults engage in the process of exploring, for example, potential occupational identities, the outcome of this process is not more or less occupational identity, or even a stronger or weaker occupational identity, but rather different types of occupational identities. Research has shown that forms of identities, occupational and otherwise, differ significantly in terms of structural features and contents [e.g., Josselson, 2003;McLean et al, 2014]. Applied to the development of moral identity, this suggests that people will ultimately develop distinct types or forms of moral identity rather than merely more or less of it.…”
Section: What Is the Endpoint Of Moral Identity Development?mentioning
confidence: 99%
“…A number of significant critiques of the centrality approach to moral identity [e.g., Nucci, 2004;Pasupathi & Wainryb, 2010a;Proulx & Chandler, 2009;Turiel & Smetana, 1984] have been proposed, on various grounds. Furthermore, the field of identity research [e.g., Erikson, 1968;Marcia, Waterman, Matteson, Archer, & Orlofsky, 1993;McLean, Syed, Yoder, & Greenhoot, 2014] suggests important considerations in studying identity of any kind -considerations that are overlooked in the centrality approach. In the remainder of our commentary, we consider how one might build from some of the existing critiques and findings an alternative way of thinking about moral identity -one that allows for examining normative developmental changes as well as a broader range of individual differences and, ultimately, also the development of individual differences and specific forms of moral identity.…”
mentioning
confidence: 99%
“…Here, I would argue that it seems quite effective for an experience of racial bullying to change a person's perspective on the world rather than on the self. While narrative researchers have long argued that what is most important in a narrative is the subjective meaning of an event as opposed to its objective content, more recent perspectives are now suggesting that event content and identity process may intersect in important and dynamic ways within the life story [McLean & Pasupathi, 2012;McLean, Syed, Yoder, & Greenhoot, 2014;Syed & Azmitia, 2010].…”
mentioning
confidence: 99%